Hubungan Pengetahuan Dan Sikap Ibu Hamil Dengan Kejadian Kekurangan Energi Kronik Di Puskesmas Labuhan Deli Kecamatan Medan Deli Kabupaten Deli Serdang Tahun 2023 - Sonia Novita Sari; Nurkholidah Pulungan; Marlina Lamawati Simbolon (Lembaga Pengembangan Kinerja Dosen, 2024)
Chronic energy deficiency is a condition of pregnant women who suffer from a long-term (chronic) lack of food with the emergence of various health problems in pregnant women. The aim of this research is to determine the relationship between the knowledge and attitudes of pregnant women and the incidence of chronic energy deficiency at the Labuhan Deli Community Health Center, Labuhan Deli District, Deli Serdang Regency, Deli Serdang Regency. Quantitative design using cross sectional. The population in this study was pregnant women, totaling 42 respondents. Data analysis uses univariate, bivariate analysis. The results of this study show that there is a relationship between the knowledge and attitudes of pregnant women and the incidence of chronic energy deficiency at the Labuhan Deli Community Health Center, Labuhan Deli District, Deli Serdang Regency, Deli Serdang Regency in 2023. Suggestions are given for research and for research sites and for institutions Education about CED for pregnant women.